2015
DOI: 10.1038/bmt.2015.319
|View full text |Cite
|
Sign up to set email alerts
|

Favorable long-term outcome of patients with multiple myeloma using a frontline tandem approach with autologous and non-myeloablative allogeneic transplantation

Abstract: Despite survival improvement with novel agents and use of autologous hematopoietic stem cell transplantation (HSCT), cure of patients with multiple myeloma (MM) remains anecdotal. Initial observations suggested that chronic GvHD was accompanied by an anti-myeloma effect after myeloablative HSCT, but unfortunately this procedure was hampered by high non-relapse mortality (NRM). To maximize the anti-myeloma effect and minimize NRM, we developed a non-myeloablative (NMA) regimen associated with a high incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…In the trials involved in our meta-analysis, 55 [ 10 15 , 17 , 19 25 , 27 36 , 38 – 52 , 57 65 , 67 73 ] trials reported grades 2–4 acute GVHD (aGVHD) with the incidence varying from 2.3 to 69.6%, 38 trials [ 10 , 11 , 13 , 14 , 21 , 23 , 25 , 27 30 , 32 34 , 36 , 38 , 40 42 , 44 , 45 , 47 50 , 52 , 58 , 59 , 61 , 63 65 , 67 70 , 72 , 74 ] reported extensive chronic GVHD (cGVHD) with the incidence ranging from 5.3 to 79.3%, and 30 trials [ 11 , 13 , 22 , 23 , 25 , 27 34 , 36 – 38 , 40 , 42 , 44 , 45 , 48 50 , 58 , 59 , 63 , 64 , 68 , 69 , 72 ] reported limited cGVHD with the incidence varying from 5.1 to 46.3%. There were significant heterogeneity in the pooled estimates of the incidence of aGVHD (p = 0, I 2 = ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the trials involved in our meta-analysis, 55 [ 10 15 , 17 , 19 25 , 27 36 , 38 – 52 , 57 65 , 67 73 ] trials reported grades 2–4 acute GVHD (aGVHD) with the incidence varying from 2.3 to 69.6%, 38 trials [ 10 , 11 , 13 , 14 , 21 , 23 , 25 , 27 30 , 32 34 , 36 , 38 , 40 42 , 44 , 45 , 47 50 , 52 , 58 , 59 , 61 , 63 65 , 67 70 , 72 , 74 ] reported extensive chronic GVHD (cGVHD) with the incidence ranging from 5.3 to 79.3%, and 30 trials [ 11 , 13 , 22 , 23 , 25 , 27 34 , 36 – 38 , 40 , 42 , 44 , 45 , 48 50 , 58 , 59 , 63 , 64 , 68 , 69 , 72 ] reported limited cGVHD with the incidence varying from 5.1 to 46.3%. There were significant heterogeneity in the pooled estimates of the incidence of aGVHD (p = 0, I 2 = ...…”
Section: Resultsmentioning
confidence: 99%
“…37 [ 10 13 , 15 , 19 , 20 , 22 , 24 , 26 28 , 31 33 , 36 , 38 , 40 , 42 45 , 47 50 , 57 60 , 64 67 , 69 , 72 , 73 ] out of 61 trials reported the results of RR with the incidence ranging from 14.3 to 91.3%. The pooled estimate (95% CI) for RR was 50 (95% CI 45–55%).…”
Section: Resultsmentioning
confidence: 99%
“…We and others reported a promising post transplantation strategy using pre-emptive DLI along with IMiDs and/or cyclophosphamide, and prospective trials are warranted [136, 143, 144]. A number of smaller, non-controlled allo SCT studies have also been published reporting long term survival even in patients with high risk cytogenetics [130, 134, 145148]. The later suggests that allo SCT might be able to overcome adverse cytogenetic features, and justifies further clinical evaluation in this group of patients.…”
Section: Allogeneic Stem Cell Transplantationmentioning
confidence: 99%
“…The role of allogeneic stem cell transplantation (alloSCT) as treatment option for relapsed MM is currently under debate. [2][3][4][5][6][7][8] However, important lessons can be learned from the effect of T-cell therapy in the context of alloSCT. This may help to further develop T-cell therapy exploiting chimeric antigen receptor (CAR) cells, which is increasingly being performed.…”
Section: Introductionmentioning
confidence: 99%